Investigating the Impact of Perceived Elements of Social Media Marketing on Consumer Brand Interaction and Brand Knowledge in the Fashion Industry - Rostamzadeh , Reza; Develi, Evrim Ildem; Ghorbani, Shahryar; Streimikis, Justas; Kot, Michal (Transformations In Business & Economics, 2025)
In the digital economy of today, social media has transformed marketing functions in most consumer-oriented businesses, such as fashion. This research examines the impact of the leading social media marketing features – “entertainment”, “customization”, “electronic word of mouth” (EWoM), and “trendiness” – on “consumer brand engagement” and “brand awareness” in the fashion industry. Based on a systematic survey conducted among 384 active social media users, the study uses partial least squares structural equation modeling (PLS-SEM) to analyze the interrelatedness of the variables. The study reveals that “consumer engagement” with brands is highly influenced by EWoM, interactivity, and “fashion trends”, which consequently increase “brand awareness” and “brand image”. However, the influence of “entertainment” and “customization” on consumer participation was statistically insignificant. Through offering a strict examination of the determinants of “brand knowledge” in social media contexts, this research provides fresh insights into digital marketing strategies and offers pragmatic implications for practitioners who wish to maximize consumer participation in fashion-based brand communities.
Keywords: social media marketing; consumer engagement; brand awareness; fashion industry; brand image